(untitled) (Journal of the Entomological Research Society, 2018)
Five tachinid species were reared from five different hosts. Two of the hosts are recorded for the first time. These two host-parasitoid couples are Apterogenum ypsillon (Denis and Schiffermüller, 1775) (Noctuidae) for Pales pavida (Meigen, 1824) and Ephelis cruentalis (Geyer, 1832) (Pyralidae) for Clemelis pullata (Meigen, 1824). Also, four new host records for Turkey were identified.